BAY‘AH: IDEOLOGI PEMERSATU DAN NEGOSIASI MASYARAKAT DI RUANG PUBLIK - Sumardi, Dedi (Universitas Islam Negeri Mataram, 2017)
Abstract: This article aims to analyse the rise of bay‘a. It is often perceived ofthe seed of early civilised society after passing through a series of negotiationinvolving primordial and territorial interests. Theoretically, ba‘ya is a form ofrelationship between religion and the state that integrate citizens regardlesstheir race, ethnicity and colour in a public space. This article argues that Islamappears to be the pioneer of the concept of unity in public space, which wasalways in a state of competition leading to tensions and conflicts on the groundof primordial identities. The bay‘a was exactly a response to such tensionon public space. It promotes “awareness of plurality” to combat horizontalconflict between race and ethics. In the global context, this awareness is partof the argument of legal pluralism to analyse several primordial interests,and also to prevent social conflict. So, plural identities can be unified by Islamthrough bay‘a as a concept whose realization is able to unify plural society inpublic domains. Abstrak: Artikel ini bertujuan menganalisis munculnya konsep bay‘ahsebagai cikal bakal terbentuknya masyarakat berperadaban setelah melaluiproses negosiasi yang sarat dengan berbagai kepentingan primordial danteritorial.Secara empiris, bay‘ah adalah bentuk lain dari hubungan agamadan pemerintahan-untuk tidak menyamakan- dengan istilah negara modernmemberi insiprasi untuk menangkap sekat-sekat yang terpisah oleh hubunganemosional didasarkan oleh ras, suku maupun warna kulit. Tulisan iniberpendapat bahwa Islam tampil sebagai pencetus konsep pemersatu di ruangpublik khususnya kepada masyarakat yang senantiasa mengusung identitassektoral dan primordial. Konsep bay‘ah tidak terlepas dari adanya ”kesadaranterhadap keberagaman” dalam mengakhiri konflik horizontal antar sesama suku dan etnis. Dalam konteks global ”kesadaran keberagaman” adalah bagiandari argumen pluralisme hukum dalam menganalisis berbagai kepentinganprimordial untuk menghindari terjadinya konflik sosial, sehingga keragamanidentitas berhasil disatukan oleh Islam dalam satu ideologi pemersatumasyarakat di ruang publik yang diterima semua komunitas.